2020
DOI: 10.1186/s12889-020-09388-9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice (KAP) survey of canine rabies in Khyber Pakhtunkhwa and Punjab Province of Pakistan

Abstract: Background: This study aimed to assess the extent of knowledge and understanding of rabies disease in rural and urban communities of Pakistan. It also identified malpractices after suspected dog bite that might pose a risk for humans contracting rabies. Methods: A cross-sectional study was conducted (n = 1466) on people having different age groups and educational levels in four different geographic regions of Punjab and Khyber Pakhtunkhwa provinces in Pakistan. Knowledge, attitude, and practices of people were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 28 publications
2
26
5
Order By: Relevance
“…Knowledge, attitudes and practice (KAP) surveys can be used in disease control programs to identify misconceptions, misunderstandings and behaviours that might constitute barriers in the implementation of interventions (Chenais et al., 2017; Krentel et al., 2006; Matibag et al., 2007). In the context of disease control, KAP surveys are based on the assumption that knowledge leads to behaviour and practices against disease and thus, to changes that lessen the disease impact (Ahmed et al., 2020; Mascie‐Taylor et al., 2003). Therefore, a better understanding of the KAP of stakeholders towards a disease can help to identify if awareness campaigns could be necessary or if stakeholders are likely to comply with measures to reduce the disease spread.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge, attitudes and practice (KAP) surveys can be used in disease control programs to identify misconceptions, misunderstandings and behaviours that might constitute barriers in the implementation of interventions (Chenais et al., 2017; Krentel et al., 2006; Matibag et al., 2007). In the context of disease control, KAP surveys are based on the assumption that knowledge leads to behaviour and practices against disease and thus, to changes that lessen the disease impact (Ahmed et al., 2020; Mascie‐Taylor et al., 2003). Therefore, a better understanding of the KAP of stakeholders towards a disease can help to identify if awareness campaigns could be necessary or if stakeholders are likely to comply with measures to reduce the disease spread.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in India found some participants had heard about rabies, but knowledge of first-aid following a bite was poor, with application of chillies, turmeric or kerosene and visiting traditional healers recommended [ 33 , 35 , 37 ]. In two Pakistan studies, most participants stated there had been no rabies awareness campaign in their community [ 28 , 38 ], with similar findings in India [ 32 , 35 ]. People reported getting their information from friends, family and neighbours, with women who had received no formal education likely to be less aware of the disease [ 32 ].…”
Section: Resultsmentioning
confidence: 80%
“…Ahmed and colleagues found people bitten by dogs in Pakistan did not seek post-exposure prophylaxis or vaccinate their domestic dogs even when aware of the existence of vaccination programmes. This was true despite 70% of participants knowing rabies was a vaccine-preventable disease and 75% understanding that it was fatal [ 28 ]. Similar responses were found in Bangladesh, with most participants (32%) not treating bite wounds before attending hospital for post-exposure prophylaxis, 22% applying antiseptic or water, 14% applying soap and water, and 15% applying products such as lime, soda, salt and kerosene oil [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the study of Ahmed et al . [ 14 ] in India, where 72.4% of respondents were aware that rabies is a fatal disease, the proportion of recognition in Benin is markedly less.…”
Section: Discussionmentioning
confidence: 99%